Revisit Intention Wisatawan di Taman Tematik Kota Bandung - Octaviany, Vany; Utami, Dwiesty Dyah (Universitas Pendidikan Indonesia, 2017)
One of the tourist attraction that is in interest in the city of Bandung is a theme park. Bandung thematic park managers as one tourist attraction that can attract tourists to continue to come to the city of Bandung need to understand how to make the tourists feel satisfied and come back for a tour in the city of Bandung, considering now many areas in Indonesia that develop shopping tourist attractions and culinary that has been popular by tourists in the city of Bandung. Therefore, the researcher raised the factor of tourist intention or revisit of tourist intention in Bandung thematic theme park as research theme. This research is descriptive research. Research method used in this research is explanatory survey, the sample to be studied is a number of 150 people by using systematic random sampling Based on the results of research revisit intention in Bandung Thematic Park has a high assessment. It shows that the tourists who come to the theme parks of Bandung City are satisfied with thematic parks they visit, so intend to re-visit and have the desire to recommend thematic parks Bandung to others.